Anxiety and Depression Disorder Among Young Cannabis Users in Tunisia. (1st June 2022) - Brahim, S.; Henia, M.; Haj Mohamed, A.; Chabbouh, M.; Zarrouk, L.
Abstract : Introduction: The use of cannabis is likely to increase as regulations on its consumption are diminishing throughout the world. Objectives: to identify the prevalence of anxiety and depression symptoms in a group of cannabis users in Tunisia. Methods: this a transversal descriptive study about 137 participants in the University Hospital Of Mahdia during 2 months. Results: In our study population, the consumers were young adults aged between 18 and 35 years old, of whom 40.8% were professionally active, 23.2% had psychiatric history. Moreover, the use of other substances was regular among users as follows: tobacco among 74.6% of users, alcohol among 72.5% of users, ecstasy among 41.3% of users, cocaine among 25.4% of users. The use of cannabis was considered as a means of exultation for 66.7%, as an anxiolytic for 26.8% and as a sedative for 23.9%. Overall, the effect of cannabis use on anxiety and depression on the HAD scale showed the following results: probable anxiety in 53% of cases, probable state of depression in 72% of time. Conclusions: The correlation between cannabis use, anxiety and depression remains unclear. Equally concluded, the assumption of self-medication by cannabis stills a topic of discussion. Disclosure: No significant relationships.